2009
DOI: 10.1007/s10658-009-9545-9
|View full text |Cite
|
Sign up to set email alerts
|

Seed treatments enhance photosynthesis in maize seedlings by reducing infection with Fusarium spp. and consequent disease development in maize

Abstract: Maize seed that was either treated with the fungicide Cruiser Extreme 250 ® (fludioxonil + azoxystrobin + mefenoxam + thiamethoxam) or not treated was planted at two Iowa locations in 2007. Root, mesocotyl and crown rot severity, incidence of Fusarium spp. colonisation and chlorophyll florescence (CF) were assessed at growth stages V2, V4 and V6, and stalk rot severity at R6. At both locations, seed treatment reduced disease severity and incidence of Fusarium spp. infection at all growth stages assessed. Measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Therefore, coating of the seed can reduce these risks. Some authors reported that seed treatments with chemicals can effectively suppress or reduce seed-borne pathogens in maize [39,40], thus reducing crown and stalk rot, while enhancing photosynthesis and improving the vigor of maize plants [41]. However, most data regard F. verticillioides [42].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, coating of the seed can reduce these risks. Some authors reported that seed treatments with chemicals can effectively suppress or reduce seed-borne pathogens in maize [39,40], thus reducing crown and stalk rot, while enhancing photosynthesis and improving the vigor of maize plants [41]. However, most data regard F. verticillioides [42].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies, which were only carried out under controlled conditions (greenhouse), have reported a significant effect of the application of a fludioxonil and metalaxyl-M mixture on the plant vigor of infected maize [14,29] or soybean [17,30], as quantified by a higher dry mass of both the shoots and roots. Moreover, Rodriguez-Brljevich [20] reported that a fungicide seed dressing suppresses the soil-borne infection of Fusarium spp. in open fields, and results in enhanced photosynthesis and increased plant vigor.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies conducted to evaluate the effect of fungicide seed treatments on Fusarium species have been performed in vitro, in growth chambers or in greenhouses to investigate the plant-fungus pathosystem in the first growth stages [3,19], while only a few experiments have taken into account the complete crop cycle under field conditions. An even smaller number have investigated the effects of fungicide seed treatments on plant growth and development until harvest [20], and in particular on grain yield [18,21]. Moreover, no information is available on the different effects of seed infection by F. graminearum and F. verticillioides from planting to harvest.…”
Section: Introductionmentioning
confidence: 99%